In situ study of sensor behavior of MoS2 field effect transistor for methyl orange molecule in ultra high vacuum condition. (24th November 2020) - Mamun, Muhammad Shamim Al; Waizumi, Hiroki; Takaoka, Tsuyoshi; Alam, Md Iftekharul; Tanaka, Yudai; Ando, Atsushi; Wang, Zhipeng; Komeda, Tadahiro
Abstract: We investigate the sensor behavior of the MoS2 field effect transistor (FET) device with the deposition of methyl orange (MO) molecule which is widely used as a chemical probe. The channel of the FET is made of the single layer of MoS2 which makes it highly sensitive to the molecule adsorption, but at the same time the behavior depends much on the surface conditions of the MoS2 channel. In order to make the channel-surface conditions more defined, we prepare an in situ experimental system in which the molecule deposition and the surface- and electrical-characterization of the MoS2 FET are executed in a single ultra-high vacuum chamber. This system makes it possible to examine the change of the FET properties with precise control of the molecule coverage in the sub-monolayer region without the effect of the atmosphere. We detected the shift of the I d – V g curve of the MoS2 -FET device with the increase of the molecule coverage ( θ ) of the MO molecule, which is quantitatively analyzed by plotting the threshold voltage ( V th ) of the I d – V g curve as a function of θ . The V th shifts towards the negative direction and the initial change with θ can be expressed with an exponential function of θ, which can be accounted for with the Langmuir type adsorption of the molecule for the first layer and the charge transfer from the molecule to the substrate. The V th versus θ curve shows a kink at a certain θ, which is conserved as the starting of the second layer growth. We detected the adsorption of MO far less than monolayer and the phase change from the first layer to the second layer growth, which is realized by the benefit of the in situ UHV experimental condition.